Effectiveness of discharge education strategies versus usual care on clinical outcomes in acute coronary syndrome patients: a systematic review. Issue 2 (February 2020) - Kourbelis, Constance M.; Marin, Tania S.; Foote, Jonathon; Brown, Alex; Daniel, Mark; Coffee, Neil T.; Newman, Peter; Beks, Hannah; Ganesan, Anand; Versace, Vincent L.; Nicholls, Stephen; Clark, Robyn A.
ABSTRACT: Objective: The objective of this review was to systematically review studies that evaluated the clinical effectiveness of hospital discharge education strategies provided to patients with acute coronary syndrome (ACS). Introduction: In an era of shortening lengths of stay for patients with ACS, bedside education opportunities are diminishing; however, the importance of discharge education on medication management, emergency procedures and safe recovery remains vital to prevent rehospitalization. Inclusion criteria: The following studies were considered for inclusion: English-language randomized controlled trials (RCTs) measuring educational strategies provided to adults with ACS as the only intervention prior to discharge or post-discharge from acute care, compared to usual care. Methods: An electronic search was performed by an experienced research librarian. MEDLINE, CINAHL, PsycINFO, Scopus, Web of Science, Cochrane Central Register of Controlled Trials, Australian New Zealand Clinical Trials Registry, ClinicalTrials.gov and WHO International Clinical Trial Registry Platform were searched for studies published between 2000 and 2017. All citations were collated and uploaded into EndNote where duplicates were removed. Titles and abstracts were screened by two independent reviewers. The reference lists of all included studies were screened for additional references. Risk of bias was assessed using the JBI critical appraisal instrument for all included studies. In the case of missing or incomplete data, corresponding authors were contacted. The primary outcomes of interest were knowledge relating to ACS diagnosis, treatment and procedures. Secondary outcomes included lifestyle modifications, medication adherence/knowledge, general practitioner follow-up, attendance to cardiac rehabilitation (CR), readmission and mortality (up to 12 months). As data were collected using different instruments in each study, meta-analysis was not performed. Results: The electronic search identified 3445 records. Following deduplication, 2093 citations were screened with 47 papers selected for assessment of eligibility. Three RCTs involving 175 participants were identified for inclusion. The certainty of this evidence (Grading of Recommendations, Assessment, Development and Evaluation) was rated as low to moderate. The risk of bias for all included studies was moderate. In all studies, the impact of inpatient educational interventions was assessed in relation to attendance to a CR program, exercise rates and medication adherence. Interventions included targeted educational sessions (15–40 minutes) where participants prioritized their learning needs and were provided tailored cardioprotective risk factor and lifestyle modification advice and invited to attend a CR program. One study presented the education in animation. In one study, intervention groups reported increased attendance to CR compared to control (47.3%; n = 9, versus 21.1%; n = 4) and another demonstrated significantly increased exercise rates from baseline to follow-up. No significant difference was reported between the intervention and control for medication adherence, and none of the studies reported readmission or mortality rates. Conclusion: The current review found little to no evidence for the effectiveness of current discharge practices on clinical outcomes. There has been limited research on modes of delivery or what the essential components for ACS discharge education should be. This review has highlighted the need for comprehensive effectiveness studies to provide a strong evidence-base to support ACS discharge practices. Systematic review registration number: PROSPERO CRD42018094781.